PLANKTON SEBAGAI PARAMETER KUALITAS PERAIRAN TELUK YOS SUDARSO DAN SUNGAI ANAFRE KOTA JAYAPURA PAPUA - Edoward Krisson Raunsai; Dolfina C. Koirewoa (NOVAE GUINEA Jurnal Biologi, 2016)
ABSTRAKTujuan penelitian adalah untuk menganalisis komposisi dan kelimpahan, tingkat keanekaragaman, keseragaman, dominansi plankton dan kualitas air di perairan Teluk Yos Sudarso dan Sungai Anafre. Pengamatan dilakukan pada perairan Teluk Yossudarso dan Sungai Anfre, dimana pada masing-masing stasiun dilakukan 3 (tiga) kali ulangan. Metode yang digunakan adalah purposive random sampling di 2 (dua) lokasi perairan dan menggunakan analisis komposisi dan kelimpahan, indeks keanekaragaman (H’), indeks keseragaman (E) dan indeks dominansi (C). Jumlah plankton di perairan Teluk Yos Sudarso 7 jenis dengan jumlah komposisi jenis 39, sedangkan jumlah plankton di kali Anafre 3 jenis, dengan jumlah keseluruhan komposisi jenis 17. Jenis Thalassioira eccentrica memiliki komposisi yang tinggi pada  Teluk Yos Sudarso (32 individu) dan Anafre (13 individu). Indeks biologi yang ditunjukkan pada perairan Teluk Yos Sudarso adalah (Kelimpahan 0,39), (H’= 0,78), (E=0,40), (C=0,67), sedangkan pada perairan kali Anafre adalah (Kelimpahan 0,17), (H’=0,67), (E=0,61) dan (C=0,61). Kata Kunci: Plankton, Parameter, Kualitas, Perairan  ABSTRACTThe purpose of the research was to analyze it’s composition and abundance, diversity, degree of uniformity, the dominance of plankton and water quality in the waters of the Bay and river Anafre Yos Sudarso. Observations made on the waters of the Gulf of Yossudarso and the river Anfre, where at each station conducted three (3) times of Deuteronomy. The method used was purposive random sampling in two (2) location of the waters and use the analysis of composition and abundance, diversity index (H'), index homogeneity (E) and the dominance index (C). The amount of plankton in the waters of the Gulf of Yos Sudarso 7 type with a total of 39 types of compositions, while the number of plankton at times Anafre 3 types, with a total number of 17 types of composition. Type of Thalassioira have a high composition eccentrica on Yos Sudarso Bay (32 individuals) and Anafre (13 individuals). Biological indices shown in the waters of the Gulf of Yos Sudarso is (the abundance of 0.39), (H ' = 0.78) (E = 0.40), (b = 0.67), while in the waters of the kali Anafre is (the abundance of 0.17), (H ' = 0.67) (E = 0,61) and (C = 0,61).Key Words: Plankton, Aquatic, Quality, Parameters